Human needs fulfillment: the contributing factors of human flourishing - Abu Bakar, Aisyah; Mohamed Osman, Mariana (Malaysian Institute of Planners, 2022)
Human Flourishing (HF) and Maslow's hierarchy of human needs are examined in this paper. Issue: The human needs hierarchy is not a zero-sum concept. The hierarchy of needs does not necessitate that people have to fully fulfil one need before moving on to the subsequent need. Recognizing human needs that are meaningful in promoting SWB, in this instance human flourishing, is crucial to comprehending the hierarchy's relevance. Purpose: This article seeks to examine the degree of human flourishing in Malaysia in relation to the difficulty and convenience of meeting human needs. Approach: Using Mann Whitney U-Tests, the median of HF across the difficulty and convenience of satisfying 24 human needs was determined. These human needs are the necessities and life conditions for which people typically and substantially strive for. Findings: The ease at which the majority of human needs may be satisfied substantially raises HF. In addition, the findings revealed that satisfying four human needs for which HF did not vary was unlikely to affect HF. Maslow's Hierarchy of Needs classified these four needs as biological and physiological needs, safety and security needs, belonging and love needs and self-actualization needs.